Crosslinked nanogel-based porous hydrogel as a functional scaffold for tongue muscle regeneration. Issue 10 (2nd July 2020) - Kinoshita, Naoya; Sasaki, Yoshihiro; Marukawa, Eriko; Hirose, Ryo; Sawada, Shin-ichi; Harada, Hiroyuki; Akiyoshi, Kazunari
Abstract: Surgical resection in tongue cancer can impair speech and swallowing, reducing quality of life. There is a need for biomaterials that can regenerate tongue muscle tissue defects. Ideally, such a biomaterial would allow controlled release of therapeutic proteins, support the survival and differentiation of therapeutic cells, and promote tongue muscle regeneration in vivo . The aim of the current study was to assess these factors in an acryloyl group-modified crosslinked nanogel, consisting of cholesterol-bearing pullulan hydrogel nanoparticles, to determine its potential as a regenerative therapeutic following tongue resection. The hydrogel demonstrated substantial porosity and underwent slow biodegradation. When loaded with a model protein, the gel enabled sustained protein release over two weeks in serum, with no initial burst release. Mouse myoblasts demonstrated adhesion to the hydrogel and cell survival was observed up to one week. Gel-encapsulated myoblasts demonstrated normal myotube differentiation. Myoblast-loaded gels were implanted in a tongue defect in mice, and there was a significant increase in newly-regenerated myofibers in gel-implanted animals. The developed biomaterial platform demonstrates significant potential as a regenerative treatment following tongue resection, as it facilitates both protein and cell-mediated therapy, and stimulates tongue muscle regeneration in vivo .